Identification of cold-inducible microRNAs in grapevine - Sun, Xiaoming; Fan, Gaotao; Su, Lingye; Wang, Wanjun; Liang, Zhenchang; Li, Shaohua; Xin, Haiping (Frontiers in Plant Science, 2015)
Low temperature is one of the most important environmental factors that limits the geographical distribution and productivity of grapevine. However, the molecular mechanisms on how grapevine responds to cold stress remains to be elucidated. MicroRNAs (miRNAs) are a class of endogenous small non-coding RNAs that play an essential role during plant development and stress responses. Although miRNAs and their targets have been identified in several Vitis species, their participation during cold accumulation in grapevine remains unknown. In this study, two small RNA libraries were generated from micropropagated ‘Muscat Hamburg’ (V. vinifera) plantlets under normal and low temperatures (4 °C). A total of 163 known miRNAs and 67 putative novel miRNAs were detected from two small RNA libraries by Solexa sequencing. Forty-four cold-inducible miRNAs were identified through differentially expressed miRNAs (DEMs) analysis; among which, 13 belonged to upregulated DEMs while 31 belonged downregulated DEMs. The expression patterns of the 13 DEMs were verified by real-time RT-PCR analysis. The prediction of the target genes for DEMs indicated that miRNA may regulate transcription factors, including AP2, SBP, MYB, bHLH, GRAS, and bZIP under cold stress. The 5’-RLM RACE were conducted to verify the cleavage site of predicted targets. Seven predicted target genes for four known and three novel vvi-miRNAs showed specific cleavage sites corresponding to their miRNA complementary sequences. The expression pattern of these seven target genes revealed negative correlation with the expression level of the corresponding vvi-miRNAs. Our results indicated that a diverse set of miRNAs in V. vinifera are cold-inducible and may play an important role in cold stress response.